2017
DOI: 10.1590/s1980-220x2016040103254
|View full text |Cite
|
Sign up to set email alerts
|

Elderly caregivers living in urban, rural and high social vulnerability contexts

Abstract: OBJECTIVE Comparing the differences in the sociodemographic, care and health profiles of elderly caregivers of the elderly living in urban, rural, and high social vulnerability contexts. METHOD A cross-sectional study developed with elderly caregivers enrolled in the Family Health Units of a municipality in the interior of São Paulo. Household interviews and evaluations were conducted on: Activities of Daily Living (ADL), self-reported pain, frailty, cognition, life satisfaction, family functionality, burden, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 19 publications
1
15
0
5
Order By: Relevance
“…This result is in agreement with data described in previous studies conducted in Brazil. 2,13,26 Approximately 30% of the participants exhibited cognitive impairment. The same rate is reported in a Chinese study involving 480 participants using the same instrument for cognitive screening (MMSE) with cutoff points adjusted for education, in which women had a greater probability of cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in agreement with data described in previous studies conducted in Brazil. 2,13,26 Approximately 30% of the participants exhibited cognitive impairment. The same rate is reported in a Chinese study involving 480 participants using the same instrument for cognitive screening (MMSE) with cutoff points adjusted for education, in which women had a greater probability of cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Interviews were conducted by trained research assistants (AB; BL; MT; ER; NO; EN) 23 at the participants’ homes, and interviews lasted between 1-2 hours. The assistants were professionals in Nursing and Gerontology fields.…”
Section: Methodsmentioning
confidence: 99%
“…These differences may be related to the family arrangements of individuals who offer care to a spouse and reside with a larger number of people, which consequently leads to a larger family income. A previous study conducted in Brazil with 343 older caregivers living in different contexts found that the majority who provided care for a spouse resided with two or three people (27) .…”
Section: Discussionmentioning
confidence: 98%